Information collection strategic design in experts-assisted decision making paradigm - Mostaghimi, Mehdi (Group Decision and Negotiation, 2001)
In an experts-assisted decision making paradigm, the information collection design becomes a strategic variable under a weak assumption that the final decision is dependent on the design used to collect information as well. As a result, the same information of the experts and the decision maker about the problem can potentially produce different final decisions for different information collection designs. The implication is that a decision maker can strategically select a design which serves his/her objective. This paper uses a Bayesian estimation methodology for combining experts' information with the decision maker's prior. An information collection process is designed by setting constraints on this model. Several designs are developed here using such controlled factors as a one-stage versus a two-stage decision process, experts' rank ordering, and group versus individual lobbying/consultation. An example is provided to illustrate the applicability of the concept. It is shown that the information produced in the process of producing a decision can also give insights into the impacts of the decision maker and the experts on the decision.
2 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/000-610-576-094-870 tex.type: [object Object]
Keywords: Bayesian method; Experts-assisted decision making; Information theory; Reaching a consensus; dept.eco; dept.fin; experts-assisted decision making; information theory; reaching a consensus